A novel method for calculating the energy cost of turning during running - Hatamoto, Y.; Yamada, Y.; Fujii, T.; Higaki, Y.; Kiyonaga, A.; Tanaka, H. (Open Access Journal of Sports Medicine, 2013)
Although changes of direction are one of the essential locomotor patterns in ball sports, the physiological demand of turning during running has not been previously investigated. We proposed a novel approach by which to evaluate the physiological demand of turning. The purposes of this study were to establish a method of measuring the energy expenditure (EE) of a 180° turn during running and to investigate the effect of two different running speeds on the EE of a 180° turn. Eleven young, male participants performed measurement sessions at two different running speeds (4.3 and 5.4 km/hour). Each measurement session consisted of five trials, and each trial had a different frequency of turns. At both running speeds, as the turn frequency increased the gross oxygen consumption (V · O2) also increased linearly (4.3 km/hour, r = 0.973; 5.4 km/hour, r = 0.996). The VO2 of a turn at 5.4 km/hour (0.55 [SD 0.09] mL/kg) was higher than at 4.3 km/hour (0.34 [SD 0.13] mL/kg) (P < 0.001). We conclude that the gross VO2 of running at a fixed speed with turns is proportional to turn frequency and that the EE of a turn is different at different running speeds. The Different Frequency Accumulation Method is a useful tool for assessing the physiological demands of complex locomotor activity.